Digital Transformation of Pedagogical Skills Among Technology and Design Course Teachers in Implementing TVET Curriculum - Wan Alida Fairuz, Wan Mohamad Hazim; Masek, Alias (Research and Innovation in Technical and Vocational Education and Training, 2025)
This study is conducted to determine the digital transformation of pedagogical skills required by Technology and Design Course (RBT) teachers in the implementation of Technical and Vocational Education (TVET) teaching. This research uses a mixed methods approach involving qualitative and quantitative analysis. Data was collected through expert interview and Fuzzy Delphi questionnaire developed and validated by an expert consisting of lecturers from higher education institutions and experienced teachers. Research findings show that there are five categories of skills that are critical for RBT teachers to meet the needs of students in an increasingly digital era. These included presentation and communication tools, data management and analysis, digital learning platforms and technologies, interactive and innovative technologies, as well as media production and editing. In addition, Fuzzy Delphi analysis was used to gain consensus on the most dominant and important skills. These findings provide valuable guidance to educators and policy makers in designing more effective training programs to improve teaching ability in the digital TVET context. In conclusion, this study not only emphasizes the importance of relevant pedagogical skills but also suggests steps to develop an educational curriculum that can meet the demands of industry and society.